Cranial Affinity among Chronological Populations in Sardinia, Italy: Biometric Insights for Orthodontic Purposes - Guglielmo Campus; Giuliana Solinas; Marco Dettori; Antonella Arghittu; Paolo Castiglia (Applied Sciences, 2023)
Since human skulls may be used as a benchmark of the evolutionary process, the aim of the present study is to assess the cranial affinity of Sardinian populations from different chronological periods, with a standard index to evaluate its benefits for orthodontic purposes. Craniometric variables from four throughout cephalograms (anterior and lateral) of 72 units from historical Sardinian populations, two prehistoric, one medieval, and one modern were compared to the Bolton standard. A one-way analysis of variance (ANOVA) was performed for means comparison. A hierarchical cluster analysis and the bootstrap technique for the reliability of the dendrogram were used. Length data revealed statistically significant results (p < 0.01). Usually, the medieval population showed higher mean values compared to the other groups; the prehistoric population presented the highest value of Euclidean distance when compared to the medieval; the modern showed no affinity to prehistoric populations nor to the Bolton standard. The length and the breadth of the neurocranium, maxillary–alveolar length, orbital height, maximum cranial breadth, and external palate breadth contributed to the dissimilarity among populations. The dissimilarities in the craniometric measurements of Sardinian populations are remarkable. Therefore, the main outcome showed that the craniometric standards of the Bolton standard are not applicable across the Sardinian population.